Developing intercultural competence through a cultural metacognition-featured instructional design in English as a foreign language classrooms - Huang, Lin (Frontiers in Psychology, 2023)
The soaring demand for intercultural competence (IC) in the globalized world has made it a key concern in foreign language education. Most existing training on IC has often focused on providing immersive intercultural experiences, equipping learners with cultural knowledge, and simulating intercultural situations. However, some of these approaches may not be feasible in English as a foreign language (EFL) classrooms, nor are they effective to prepare learners to cope with the complexities and uncertainties in novel intercultural situations unless there specifically involves higher-order thinking. Thus, this study took a perspective of cultural metacognition and examined whether and how could an instructional design that highlighted cultural metacognition facilitate learners’ IC development in an EFL classroom at the tertiary level in Chinese mainland. 58 undergraduate students enrolled in an English Listening, Viewing, and Speaking course were involved in the instruction, and questionnaires and focus groups were employed for the data collection. A paired sample t-test revealed that there was a significant enhancement in students’ intercultural competence in terms of affective, metacognitive, and behavioral dimensions, but not in the knowledge dimension. Thematic analysis indicated that the instructional design was effective in supporting students’ intentional knowledge acquiring, developing positive intercultural attitudes, and promoting the translation of cognition into actions. The findings thus confirmed that the instructional design featuring cultural metacognition can be used in domestic EFL contexts, such as College English classrooms at the tertiary level in Chinese mainland, as an effective way of enhancing learners’ IC. This study also offered additional evidence of how students’ IC development was achieved through a range of metacognitive processes, which may provide implications for teachers to design their IC instructions in similar EFL educational settings.